The evolving role of translocation t(11;14) in the biology, prognosis, and management of multiple myeloma. (May 2020) - Paner, Agne; Patel, Pritesh; Dhakal, Binod
Abstract: Cytogenetic changes in multiple myeloma (MM) have emerged as one of the most important prognostic factors. Translocations of chromosomes 4 and 14 [t(4;14)], chromosomes 14 and 16 [t(14;16)] and deletion of chromosome 17p [del(17p)] have been incorporated in the Revised International Staging System as a measure of adverse disease biology. Ongoing research is unveiling a complex genomic landscape in MM, with new cytogenetic abnormalities important for prognosis identified and the significance of known cytogenetic changes revisited. In studies conducted before the novel agent era, t(11;14) was shown to carry standard risk for patients with MM. Findings from more recent retrospective reviews have shown that t(11;14) is associated with intermediate outcomes in patients treated with novel agents as compared with patients who have standard- or high-risk cytogenetic aberrations. MM cells with t(11;14) have a unique biology, with relatively higher expression of the antiapoptotic protein BCL2 and lower expression of MCL1, in contrast to MM cells without this translocation. Translocation t(11;14) has emerged as the first predictive marker in MM, indicating susceptibility to BCL2 inhibition. Future studies will be needed to explore if the combination of novel agents with BCL2 inhibitors can improve the prognosis of patients with t(11;14). In this article, current data on the evolving role of t(11;14) in the biology, prognosis, and treatment of MM are reviewed.